γ-lactones and ent-eudesmane sesquiterpenes from the endophytic fungus Eutypella sp. BCC 13199 - Masahiko Isaka (2018)
Two new γ-lactones, eutypellins A (1) and B (2), and two ent-eudesmane sesquiterpenes, ent-4(15)-eudesmen-11-ol-1-one (3) and ent-4(15)-eudesmen-1α,11-diol (4), together with three known pimarane diterpenes, diaporthein B, scopararane A, and libertellenone C, were isolated from the endophytic fungus Eutypella sp. BCC 13199. The structures of these compounds were elucidated by interpretation of spectroscopic data. The absolute configuration of 4 was confirmed by application of the modified Mosher's method. Eutypellin A (1) and sesquiterpene 3 exhibited weak cytotoxic activities. © 2009 American Chemical Society and American Society of Pharmacognosy.